1991
DOI: 10.1063/1.461676
|View full text |Cite
|
Sign up to set email alerts
|

Selective product channels in the reactions of NH(a 1Δ) and NH(X 3Σ−) with NO

Abstract: Reactions of imidogen, NH, in the electronically excited a 1Δ and ground X 3Σ− states with NO have been studied at 300±2 K and at 20 Torr (Ar). NH(a 1Δ) and NH(X 3Σ−) were produced in the 193 nm photolysis of HNCO and CHBr3/NO, respectively, and detected by the laser-induced fluorescence (LIF) technique. Rate constants have been measured under pseudo-first-order conditions by scanning the time delay between the photolysis and probe laser pulses. Overall rate constants were determined: [4.8±0.1(2σ)]×10−11 cm3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…It is concluded that Reaction (2b) is a minor process in Reaction (2). Also, Oe P) was found to be a direct product of Reaction (1). The time lag for OH(v =0) production [which was ascribed to the exclusive production of OH in Reaction (2) in the previous study] was clearly explained by the formation of OH(v;;'I) and successive vibrational relaxation mainly by collisions with NO.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is concluded that Reaction (2b) is a minor process in Reaction (2). Also, Oe P) was found to be a direct product of Reaction (1). The time lag for OH(v =0) production [which was ascribed to the exclusive production of OH in Reaction (2) in the previous study] was clearly explained by the formation of OH(v;;'I) and successive vibrational relaxation mainly by collisions with NO.…”
Section: Introductionmentioning
confidence: 87%
“…However, the conclusion contradicted the other experimental estimates of the branching fraction for Reaction (2b)8,1l,IZ and the prediction 13 based on the potential energy surface calculation. 14 Also, Hack et al 3 measured OH in the NH + NO reaction system controlling the contribution of Reactions (1) and (2) with Xe or N 2 , and suggested that the branching ratio between H and OH production is similar for both Reactions (1) and (2).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The method developed here is based on the observation, by Kenner et al [16], that 193 nm two-photon photolysis of NH3 proceeds in part as NH3 + hυ → NH2* + H followed by NH2* + hυ → NH( [18]. The a state has been shown to be quenched by N2 [19], kQ (300 K) = (6-9) × 10 -14 cm 3 molecule -1 s -1 , which was therefore used as the bath gas and as the NH3 diluent. The highest NH fluorescence intensities were obtained by slightly defocusing the photolysis laser beam.…”
Section: Nh Productionmentioning
confidence: 99%
“…30 If it contributes to the F atom yield, then by the same arguments as presented above, it must form N 2 O with little internal excitation, a surprising result for this exothermic process.…”
Section: Addition Of No: Product Identification and Kineticsmentioning
confidence: 85%